How Business Schools Support Students Pursuing Entrepreneurship: Insights from Nepalese Students - Thapaliya, Smriti; Shah, Nitesh Kumar; Adhikari, Bibhav (Journal of Business and Social Sciences Research, 2024)
This study explores how Nepalese business schools are supporting students’ entrepreneurial aspirations and how they can further support student entrepreneurs. The study employed a qualitative research approach to gather students’ perspectives on the effectiveness of current support systems. A total of seven interviews were conducted with students from two selected business schools. From the collective responses of the students, 8 prominent roles emerged, which were analysed using thematic analysis. The findings of the study revealed that business schools have been supporting their entrepreneurial students by imparting the theoretical knowledge required for entrepreneurship, complemented by providing platforms to apply the gained theoretical knowledge in a practical setting, nurturing their entrepreneurial skills through training and mentorship, facilitating the networking opportunity, and establishing the on-campus incubation centre. However, despite the continuous efforts of the business school, findings also revealed that there are many areas to be improved and given attention to motivate students to act on their entrepreneurial ideas. Findings suggest that Business schools should give more emphasis to funding Students’ business Ideas and modernising the method of teaching. This research contributes to an understanding of fostering entrepreneurship through business education in the context of business schools in Nepal.